Merger, Acquisitions and Firm Value among Deposit Money Banks in Nigeria: A review of literature - Biodun, Kolapo Mariam; Zahra, Uthman Fatimah; Abubakar , Nafisat; Rasaq, Babatunde Alanamu; Jamiu, Abdulrasheed Alabere (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
The most frequent issues that come up during capital reconstruction include, without a doubt, overpaying for a company's value, mergers, and acquisitions. Despite these problems, this study reviewed an empirical analysis of mergers, acquisitions, and company value among Nigerian DMBs as a result of capital reconstruction. This study reviewed at least 10 pieces of literature from previous studies from which conclusions and recommendations were drawn. Thus, in accordance with the content analysis, this study draws the conclusion that, although mergers and acquisitions are complex transactions that can be challenging to complete successfully, deposit money banks can use them as a highly useful instrument to meet their strategic objectives. Therefore, this study recommends that before proceeding with any M&A transaction, deposit money banks should thoroughly consider the advantages and disadvantages of doing so.
Keywords: Merger and Acquisition; Firm Value; Capital Reconstruction; Deposit Money Banks